Família, aluno e professor: as forças tipológicas da educação básica na região metropolitana de Natal - Azevedo, ítalo Medeiros de (2013)
This work was developed in the research line: "The habitus of study: builder of a new reality in the basic education of metropolitan area Natal" which is being developed with the support of CAPES by the Centre for Education. Acts, especially the problem of academic performance of students in basic education of the public in the Metropolitan Region of Natal (RMN). Thus, the aim of this paper is to construct a typology of students in the 9th year of basic education, attending the public schools (state or municipal) of MRN, 2009, and assess, according to these profiles, what personal characteristics student and their families: economic, social and cultural capital as well as teaching practices create environments capable of favoring a good educational development as measured by the performance obtained in the assessments in mathematics and English language. The data used were provided through the microdata Brazil Exam 2009 held by INEP. We used the methods Grade of Membership (GoM) for construction of profiles relevance of students according to the characteristics already mentioned. With these profiles was verified, which were effectively generating good performance in school curriculum components evaluated. The findings indicate that students belonging to the profile considered good environment, able to achieve better school performance both in Portuguese as in Mathematics, compared to the extreme profiles and adverse deficit